Diversitas Gender, Risiko, dan Profitabilitas dalam Sistem Perbankan - Wisudanto, Wisudanto; Fikri, Muhammad Javier Annas (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2023)
This research is a response to the increasing percentage of female boards of directors in banking companies, as well as the lack of research related to gender diversity on banking credit risk and profitability. Gender diversity is observed using dummy variables, credit risk using non-performing loans, and profitability using return on assets. This study involved 112 samples and was analyzed using multiple linear regression. The results of the study show empirical evidence that the presence of the board of directors has a significant negative effect on credit risk and a positive effect on profitability. This research can be used as a consideration for shareholders when appointing the board of directors.